The Extent and Nature of Student Attrition in the First Five Years at Simon Fraser University - Mcintosh, Barbara M.; Wilson, Lolita N.; Lipinski, Beatrice G. (Canadian Journal of Counselling and Psychotherapy, 2012)
A 29% return was received of questionnaires mailed to the 4,954 undergraduates who made up the population of voluntary and administrative dropouts at Simon Fraser University during the first five years of its operation. Analysis of the responses indicated that most students left in their first year of studies, that they did not discuss their plans with university personnel, but would have liked to talk with faculty and/or administrators, that they attributed their reasons for withdrawal almost equally to academic difficulties, personal-emotional problems, and external-environmental pressures, in that order, that two-thirds of them had resumed some type of formal study, and that women were significantly less likely than men to become administrative dropouts.